Digitizing tuberculosis treatment monitoring in Wuhan city, China, 2020–2021: Impact on medication adherence - Zhang, Mengxian; Wang, Guiyang; Najmi, Hina; Yaqoob, Aashifa; Li, Tao; Xia, Yinyin; Ye, Jianjun; Hou, Shuangyi; Xiao, Ye; Zhou, Liping; Li, Yuehua (Frontiers in Public Health, 2023)
Introduction Digital technologies can improve adherence to tuberculosis (TB) treatment. We studied the impact of digitizing TB treatment monitoring on adherence among TB patients in Wuhan, China, during 2020-2021. Methods We compared an electronic system introduced to monitor TB medication adherence (e-Patient Service System; e-PSS) with the p paper-based standard of care (TB Control Information System; TCIS) in terms of prescribed TB treatment doses taken by patients and patient outcome after six months of follow up. We designed a cross sectional study using retrospective data for all drug susceptible pulmonary TB patients recorded on both systems. The main indicators were: compliant first follow up visit (within 3 days of start of treatment); medication adherence (80% or more of monthly doses taken); and end of treatment success ratio. Results A total of 1,576 TB patients were recorded in TCIS in July September, 2020 and 1,145 TB cases were included in e-PSS in January March, 2021. The distribution of patient demographic and clinical features was similar between the two groups. A larger proportion from the e-PSS group visited the community doctor in the first three days compared with the TCIS group (48.91 versus 29. 76 % respectively). Medication adherence was also higher in the e-PSS group during the 6 months of treatment than in the TCIS group (84. 28 versus 80.3 3 % respectively). Treatment success was 92.52% in the e-PSS group and 92.07% in the TCIS group. Multivariate logistic regress ion analysis demonstrated that adjusted odds ratios for compliant first follow up visit, medication adherence and favorable treatment outcome in the e-PSS versus TCIS groups were 2.94 (95% 2.47 3.50), 1.33 (95% 1.08 1.63), and 1. 12 (95% CL: 0.79 1.57) respectively. Discussion This study revealed improvements in TB care following an intervention to monitor treatment digitally in patients in Wuhan, China.